Development of a simple method to measure masseter muscle mass. (13th July 2020) - Murakami, Masaharu; Iijima, Katsuya; Watanabe, Yutaka; Tanaka, Tomoki; Iwasa, Yasuyuki; Edahiro, Ayako; Ohara, Yuki; Motokawa, Keiko; Shirobe, Maki; Hirano, Hirohiko
Abstract: Objective: To develop a simple method to estimate masseter muscle mass. Background: The masseter muscle is important for optimal oral function. A decrease in the masseter muscle mass may affect the oral and physical function of the whole body; therefore, it is an important entity to measure. However, to date, no easy measurement method has been developed for the same. Herein, we devised a simple method to estimate masseter muscle mass. In addition, we compared our method with magnetic resonance imaging (MRI) and skeletal muscle mass (SMM) to verify its validity. Materials and methods: We recorded the age, sex, masseter muscle mass (by MRI), number of retained natural teeth, number of functional teeth, length and thickness of masseter muscle, and skeletal muscle mass in 53 community‐dwelling elderly people (21 men and 32 women, average age 72.9 ± 4.5 years). The estimated masseter muscle mass was calculated by multiplying the length, width and thickness of the muscle. Results: The correlation coefficient between masseter muscle mass and estimated masseter muscle mass was r  = .903; thus, a strong correlation was recognised. The correlation coefficient between the estimated masseter muscle mass and SMM was r  = .279, considering age and sex. Conclusion: We obtained substantial results using our method for estimating the masseter muscle mass and verified its validity by comparing it with masseter muscle mass measured by MRI and SMM. We believe that our proposed technique is simple and useful for estimating masseter muscle mass.